TAJDĪD AL NAHWI ‘INDA TAMMᾹM HASSᾹN WA ATSᾹRUHU BI MᾹDATI TA’LĪMI ALNAHWI LI GHAIRI AL NᾹTHIQĪNA BI AL LUGHATI AL ‘ARABIYYAH - Bani Muhtarom, Muslih; Bani Muna, Faizul Muna; Bani Syukron, Syukron Ni'am; Bani Yasin, Yasin Syafi'i (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
Nahwu science now contains philosophy, so it isn't easy to learn. In addition, the science of nahwu compiled by classical scholars reduces it to one qorinah or guidance, namely, I'rob. Most words in Arabic end with the letter 'Ilat which cannot be identified with I'rob. The aims of this research are twofold, namely (1) to explain the new theory in nahwu science which Tammam Hassan carried out. (2) explain its effect on nahwu learning materials for non-Arabic speakers. This research is qualitative, and the type of research is library research. The data sources in this study were divided into two, namely primary with the works of Tammam Hassan and secondary with related journal articles and books. Meanwhile, the data collection technique uses documentary techniques. Meanwhile, the data analysis technique used content analysis. The result of this research is to offer tajdid al-nahwi Tamam Hassan namely al-Qarain al-Lafdziyyah. al-Qarain al-Lafdziyyah has several qorinah, including: al-I'rab, al-Rutbah, al-Shighah, al-Muthobaqah, al-Rabt, al-Tadham, al-Adat, and al-Tanghim. Its influence makes al-kalimat divided into seven, including: al-ism, al-washfi, al-fi'li, al-dhomir, al-dzorof, al-kholifat, and al-'adat. then al-Zaman is divided into two namely al-zaman al-nahwi and al-zaman al-shorfi. while al-dhomir is divided into two namely al-Khudur and al-Ghoibah. then al-Khudur includes al-takallam, al-khatab, al-isyarah while al-Ghaibah includes al-Syakhsiyah and al-Mausufiyah. With al-qarain al-lafdziyah, it greatly influences broader and understanding nahwu learning. Therefore, researchers, educators, and students must explore it.